Occupying the Red Line--Radical Education, One Subway Car at a Time - Ramsey, Joe (Radical Teacher, 2013)
We work in teams of three or four, starting at the back of the train (in Davis Square, Somerville), and working our way forward, car by car, as the Red Line heads South (towards Ashmont, Dorchester).  We carry stacks of leaflets, stickers, bundles of Boston Occupier newspapers, clipboards tucked under our arms—a band of guerilla radical educator-agitators, the revolution underground, riding the rails.